Workers in Australian prebake aluminium smelters: update on risk of mortality and cancer incidence in the Healthwise cohort. Issue 3 (31st January 2023) - Del Monaco, Anthony; Dimitriadis, Christina; Xie, Sophia; Benke, Geza; Sim, Malcolm Ross; Walker-Bone, Karen
Abstract : Objectives: To investigate mortality and the rates of incident cancer among a cohort of aluminium industry workers. Methods: Among 4507 male employees who worked in either of two Australian prebake smelters for at least 3 months, data linkage was undertaken with the Australian National Death Index and Australian Cancer Database. Standardised Mortality Ratios (SMRs) and Standardised Incidence Rates (SIRs) were estimated for the whole cohort and for: production; maintenance and office workers. SMRs and SIRs were calculated by time since first employment. Results: Among production workers, there was an excess risk of mortality from mesothelioma (SMR 2.8, 95% CI 1.3 to 5.2), lung (SMR 1.4, 95% CI 1.0 to 1.8), prostate (SMR 1.9, 95% CI 1.3 to 2.7) and liver cancer (SMR 2.0, 95% CI 1.1 to 3.4) and the SIR was also increased for overall respiratory cancers, specifically lung cancers. An excess risk of death from stomach cancer (SMR 2.9, 95% CI 1.2 to 6.1) and Alzheimer's disease (SMR 3.4, 95% CI 1.1 to 7.9) was seen among maintenance workers. The overall risk of death was similar to that of the Australian general population, as was mortality from cancers overall and non-malignant respiratory disease. Conclusions: No excess risk of death from bladder cancer or non-malignant respiratory disease was found. Excess lung cancer mortality and incidence may be explained by smoking and excess mortality from mesothelioma may be explained by asbestos exposure. An excess risk of mortality from liver and prostate cancer has been shown in production workers and requires further investigation.